1998
DOI: 10.1046/j.1365-2141.1998.00810.x
|View full text |Cite
|
Sign up to set email alerts
|

Linkage of four polymorphisms on the αIIb gene

Abstract: The subunits of the platelet integrin alphaIIb beta3 are encoded by two genes located on chromosome 17. Two pathologies are associated with structural modifications of this complex: Glanzmann's thrombasthenia and alloimmune thrombocytopenia. The former is a hereditary bleeding disorder, the latter is due to an immune response linked to the presence of specific epitopes defined by single amino acid substitutions called human platelet alloantigen (HPA) systems. Analysing the alphaIIb gene from 112 independent ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…T in exon 30 were in complete linkage disequilibrium. This was previously reported along with a fourth polymorphism involving a 9-bp deletion in intron 21 [23].…”
Section: Discussionmentioning
confidence: 74%
“…T in exon 30 were in complete linkage disequilibrium. This was previously reported along with a fourth polymorphism involving a 9-bp deletion in intron 21 [23].…”
Section: Discussionmentioning
confidence: 74%
“…The patient was found to be heterozygote for HPA‐3a/HPA‐3b. The differences for the fragments containing exon 22 and exon 30 corresponded to two new silent polymorphisms which are also linked to the HPA‐3 system ( Ruan et al , 1998 ). In contrast, the two altered patterns seen for fragments containing exon 12 and exon 18 did not correspond to any known polymorphisms of the GPIIb gene.…”
Section: Resultsmentioning
confidence: 99%
“…The first four variants have already been reported to be reciprocally linked and found in homozygosis in individuals with normal platelet aggregation responses. 24 Exon-trapping analysis of a genomic DNA fragment containing the variant intron 21 indicated that it does not have a significant impact on αIIb gene expression at the transcription level. Both alleles generated similar amounts of transcripts, but a scarce additional RT-PCR product was obtained from the variant αIIb allele (Online Supplementary Figure S1B).…”
Section: Identification Of the L718p Mutation In β3mentioning
confidence: 99%